A study on consumers needs among Indonesian migrant towards Celcom International Business Division / Ammei Asraf Ab.Ghani - Ab.Ghani, Ammei Asraf (Faculty of Business and Management, 2009)
As a telecommunication company, customers are the most importance key in the Celcom Malaysia Bhd as the business nature. The satisfaction of the customer will ensure the business growth and the strengths to compete with other rivals in the market. Based on this believe, this study was conducted which is to know whether Celcom Malaysia Bhd is fulfilling the customer needs especially migrants in their life. For the Chapter 1 explains the introduction of the case study. Chapter 2 is explaining the background of study, while Chapter 3 identifies the issue/problem identification. In Chapter 4 will discuss the literature review and the chapter is Chapter 5 will share the research methodology, followed by finding and lastly conclusion and recommendation. The finding shows the migrants are not satisfied with the services provide by Celcom and Celcom need to take an action to overcome the dissatisfaction among the migrants as migrants are their main target market.